Does Fintech Lending And ICT Development Index Affect Poverty? Evidence From Indonesia - Handy Nugraha; Santi Putriani (Jurnal Reviu Akuntansi dan Keuangan, 2023)
Purpose: The purpose of this research is to see how FinTech Lending and ICT Development Index affect poverty in Indonesia. This study provides knowledge about the impact of FinTech Lending and the ICT Development Index on poverty reduction. Methodology/approach: This study uses a quantitative approach and panel data regression analysis method. This study uses panel data consisting of 34 provinces in Indonesia with observations for 2019-2021. This study uses secondary data types obtained from official Indonesian government agencies (OJK and BPS). Findings: The results of this study found that the FinTech Lending and ICT Development Index have a negative effect on poverty in Indonesia. This means that the growth of FinTech Lending and ICT can reduce poverty in Indonesia. Practical implications: The results of this research can be considered by policymakers to support FinTech development and financial inclusion, as well as increase budget allocations for the acceleration and equity of ICT infrastructure development which in turn can help reduce poverty in Indonesia. Originality/value: To the best of the researcher's knowledge, this study is the first study to link FinTech, ICT Development Index, and Poverty simultaneously in Indonesia.